Relações sociais no trabalho híbrido: uma comparação entre os três modelos atuais de trabalho - Ruas, Gabriella Soares (Universidade Federal de São Carlos, 2024)
With the advent of globalization and the advance of technology, new work models were established, such as the possibility of working from home, a scenario that was strengthened by the COVID-19 pandemic. Therefore, the main objective of this research project is to compare the three current work models, allowing a conclusion about the most appropriate model given the categories analyzed. To achieve these results, quantitative and qualitative methods were used through surveys and interviews. The results found were favorable to the adoption of the hybrid work model with the Transport, Working Hours and Salary categories being listed as the 3 main advantages, while the 100% in-person model came in last place in the ranking due to the same issues.
Social relationships in hybrid work: a comparison between the three current work models
Keywords: Trabalho Híbrido; Pertencimento; Relação Social; Hybrid Work; Belonging; Social Relationship; ENGENHARIAS::ENGENHARIA DE PRODUCAO